PEMBERDAYAAN PEREMPUAN MELALUI INOVASI BOLU UBI KAYU DAN MEDIA SOSIAL BERSAMA KARANG TARUNA DI DESA PETANANG KECAMATAN LEMBAK KABUPATEN MUARA ENIM - Romli; Putri Febiyanti; Sarah Sumayyah; Rani Rahmadani; Puput Nur Rasio; Adinda Nurhasanah; Aderia Pramita; Adinda Andle Putri (DEVELOPMENT: Journal of Community Engagement, 2026)
Women’s empowerment is a key strategy to enhance rural economic independence through the development of local potential-based enterprises and the utilization of digital technology. In Petanang Village, Lembak District, Muara Enim Regency, women process cassava into crackers; however, product innovation and marketing remain limited to conventional methods. This community service program aimed to improve women’s capacity through cassava sponge cake innovation and the optimization of social media with the assistance of the local youth organization (Karang Taruna) as digital facilitators. The method applied was a participatory approach involving observation, product innovation training, and digital marketing assistance. The results indicated an improvement in participants’ skills in producing value-added products and utilizing social media for promotion. This program has the potential to serve as a sustainable empowerment model for women-led MSMEs based on local resources and digital literacy. Keywords:  Cassava Cake, Social Media, Women’s Empowerment, Village MSMEs, Product Innovation